Low Serum Vitamin E Levels Positively Correlate with the Severity of Acne Vulgaris - Indry Salonika Sutiawan; Ketut Kwartantaya Winaya; Nyoman Suryawati; Luh Made Mas Rusyati; I Gusti Ayu Agung Dwi Karmila; Ni Made Dwi Puspawati (Universitas Malahayati, 2024)
ABSTRACT Acne vulgaris (AV) is a common disorder of the pilosebaceous, especially prevalent in adolescents. Acne vulgaris ranks among the top ten most prevalent diseases globally. Although AV may resolve spontaneously, sequelae such as scar formation can persist, causing aesthetic and psychological disturbances. There is an antioxidant to counteract acne-causing oxidative stress, vitamin E, which is an important antioxidant in the human body. Therefore, vitamin E in the skin can reduce the formation of squalene peroxide and prevent the occurrence of AV. This is an analytical observational study using a cross-sectional design. The investigation was conducted at the Dermatology and Venereology Clinic of Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital and the laboratory of the Faculty of Medicine, Udayana University, from February 2024 until the sample size was fulfilled. The sample consisted of patients aged 12-45 years with acne vulgaris who visited the clinic and were then selected through consecutive sampling according to the inclusion and exclusion criteria. In the non-AV group, the mean serum vitamin E level was 19.3 ± 0.99 µg/ml, whereas in the AV group, it was 4.49 ± 19.1 µg/ml, indicating a significant variance. There was a positive correlation between low vitamin E levels and the severity of AV. The linearity graph shows the direction of the relationship between serum vitamin E levels and the severity of AV, which leads to the lower right, indicating that the higher the severity of AV, the lower the serum vitamin E levels. The mean levels differed significantly between the non-AV and AV groups. A favorable association was found between low vitamin E levels and the severity of AV. Keywords: Acne Vulgaris, Severity, Serum Vitamin E, Reactive Oxygen Species (ROS)